TUMOR GANAS OVARIUM RESIDIF METASTASIS KARSINOMA MUSIN KE UMBILIKUS, PERITONEUM, DAN CAIRAN ASITES TANPA DITEMUKAN TANDA KEGANASAN PADA PEMERIKSAAN HISTOPATOLOGIS PASCA OPERATIF SEBELUMNYA - Arif Fadillah; Andi Friadi (Andalas Obstetrics And Gynecology Journal, 2019)
Background : Malignant ovarian tumor are still the number one cause of death and the second most  of incidents for gynecological malignant tumors. The principles of management of ovarian cancer are the same as the principles of handling other malignant diseases, for the treatment of primary lesions operatively and the handling of potential sites of tumor metastases with chemotherapy. Histopathological examination is still considered a gold standard for diagnosis and definitive treatment of malignant ovarian tumors. If histopathologic results are obtained, then the patient will be planned to undergo postoperative chemotherapy. The mismatch between the preoperative and intraoperative clinical features, and the results of postoperative histopathological examination is a problem in managing cases of ovarian malignant tumors.Objective : Report a case of residive ovarian carcinoma with no appearance of malignancy marker in the previous postoperative histopathological examination.Method : Case reportCase : We report the case of a 45-year-old woman with a history of two previous laparotomy. The first operation was carried out in February 2014 on the indication of an extra ovarian cyst, resulting in the impression of a "Follicular Cysts" based on histopathological examination. The second operation was performed in March 2015, performed surgical staging tumors with an indication of malignant ovarian tumors with clinical metastases, but from histopathological examination it was found that "Cystadenoma Ovarii Muscinosum Multiloculare" and "no visible signs of malignancy", so the patient was not managed with postoperative chemotherapy. In April 2019 patients came with complaints of new mass growth, from CT-Scan and USG investigations there was a suspicious impression of a residive ovarian tumor with metastases into the omentum and massive ascites. On May 16, 2019 an optimal debulking was performed with the findings of residive mass, ascites, and mass metastases in the intra operative peritoneum. From the results of histopathological examination, it was found that "Muscinous Carcinoma with metastases to the umbilicus, peritoneum, and ascitic fluidKeywords: Malignant residive ovarian tumor, mucinous ovarian carcinoma